Laboratory markers of multiple organ pathology in severe cases and adverse outcomes of SARS-CoV-2 infection (systematic review) - N. A. Konyshko; L. I. Volynets; G. S. Konyshko (Журнал инфектологии, 2023)
The aim of the review: to present up-to-date scientifically based information about the laboratory parameters of patients associated with severe SARS-CoV-2 infection and internal organ damage. Materials and methods: full-text publications of clinical, randomized and cohort studies, systematic reviews and meta-analyses from scientific databases PubMed, Elsevier, Scopus, Google Scholar, E-library for the period from 2019 to 2022 were analyzed. Results. Specific biomarkers were identified, including inflammatory and immunological parameters (C-reactive protein, procalcitonin, IL6), hematological (number of lymphocytes and neutrophils, NLR, D-dimer, ferritin, RDW), myocardial (troponin, creatinekinase-MB, myoglobin), hepatic (AST, ALT, total bilirubin, albumin) and characterizing lung injury (KL-6), which can be used for risk stratification, as prognostic biomarkers of adverse clinical consequences, including death in patients with COVID-19. The studies demonstrated new biomarkers of inflammatory and systemic manifestations of COVID19: procalcitonin, calprotectin and presepsin.